The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/tbj.13372
|View full text |Cite
|
Sign up to set email alerts
|

Once‐weekly hypofractionated radiotherapy for breast cancer: First results of a phase II clinical trial

Abstract: Hypofractionated radiotherapy (HF) in 15 or 16 daily fractions is well established as an alternative in early breast cancer after breast‐conserving surgery. Evidences for a whole‐breast treatment even shorter, in 5‐10 fractions, are still scarce. Women 50 years or older, with early breast tumor (pT1‐2pN0), after breast‐conserving surgery were eligible to enter in this phase II trial and received whole breast once‐weekly hypofractionated radiotherapy (wHF‐RT) to a total dose of 30 Gy, in 5 fractions of 6 Gy. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Considering moderate–severe acute toxicity at the end of RT, both erythema, edema and epitheliolysis rate did not exceed 10%, in agreement with previous studies (Ortholan et al 2005 ; Rovea et al 2015 ; Bonzano et al 2019 ). This data represents a better result compared to other group findings (Dragun et al 2013 ; Sanz et al 2018 ; Reboucas et al 2019 ), although Dragun et al and Reboucas et al rated toxicity with a different scale (CTCAE version 3.0). Furthermore, in our report only one G3 erythema was recorded, confirming severe acute toxicity was negligible/minor.…”
Section: Discussionmentioning
confidence: 46%
“…Considering moderate–severe acute toxicity at the end of RT, both erythema, edema and epitheliolysis rate did not exceed 10%, in agreement with previous studies (Ortholan et al 2005 ; Rovea et al 2015 ; Bonzano et al 2019 ). This data represents a better result compared to other group findings (Dragun et al 2013 ; Sanz et al 2018 ; Reboucas et al 2019 ), although Dragun et al and Reboucas et al rated toxicity with a different scale (CTCAE version 3.0). Furthermore, in our report only one G3 erythema was recorded, confirming severe acute toxicity was negligible/minor.…”
Section: Discussionmentioning
confidence: 46%
“…It is documented that up to 95% of patients who undergo radiotherapy will develop moderate-to-severe skin reactions [19]. Randomized trials showed that 3-week schedule of 40 Gy had less acute and late skin toxicity events compared to the conventional 5-week schedule radiotherapy for breast cancer [20][21][22]. In FAST-Forward trial late normal tissue skin effect were worse for 27 Gy compared to 40 Gy at 5 years follow-up, but similar for 26 Gy in 5 fraction schedule [9].…”
Section: Discussionmentioning
confidence: 99%
“…Excellent or good cosmesis was 82.3%, and 17.7% was average or poor. Rebouças et al 22 presented the initial results of toxicities for a prospective phase II study. The prescribed dose was 30 Gy into five fractions of 6.0 Gy, one fraction weekly, without a supplementary dose at the tumor bed.…”
Section: Hyper-hypofractionation-retrospective and Prospective Studiesmentioning
confidence: 99%